PENGARUH BUDAYA KERJA, MOTIVASI DAN JAMINAN SOSIAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PABRIK ROKOK BAGIAN LINTING PT. GENTONG GOTRI SEMARANG - Puspita, Marisa Widya; Waluyo, Handoyo Djoko; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Labor as resources who have skills, potential and creativity need to be developed as optimal as possible to be able to achieve the success of the company. Employee productivity is affected by several factors, including the work culture, motivation and social security. Decrease employee productivity are caused by less good work culture, lack of motivation and lack of social security services. PT. Gentong Gotri Semarang as one of the organization of a business which moves in the tobacco industry inside of them there are roll departement employees who are actively involved in activities company every day which is the production of cigarette.This study aims to identify and explain the effect of cultural work , motivation and social security on employee productivity cigarette factory roll departement at PT. Gentong Gotri Semarang. This research uses research tipe explanatory approach to 75 respondents with purposive sampling technique sampling. Data collection techniques in this study using the technique of interviews, questionnaires, observation and study of literature. The analysis technique used is qualitative and quantitative. Quantitative analysis using frequency table, cross-table analysis, validity test, reliability test, simple linear regression, multiple linear regression and tests of significance (t test and F test) with the help of SPSS program for Windows version 20.0.Results of statistical analysis known partial effect between the working culture and employee productivity of 29,2%, then the motivation with employee productivity equation of 33,5%. While the social scurity with employee productivity of 23%. Simultaneous influence cultural work, motivation and social security on employee productivity of 36,2% while 63,8% is influenced by other factors.Recommendations for improving employee productivity for the company to increase its attention to the work culture, motivation and assurance which in turn will ultimately increase employee productivity from employees.